The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.analchem.2c01132
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Electrochemiluminescence for Visual Simultaneous Detection of RASSF1A and SLC5A8 Tumor Suppressor Gene Methylation in Thyroid Cancer Patient Plasma

Abstract: Visual one-step simultaneous detection of low-abundance methylation is a crucial challenge in early cancer diagnosis in a simple manner. Through the design of a closed split bipolar electrochemistry system (BE), detection of promoter methylation of tumor suppressor genes in papillary thyroid cancer, RASSF1A and SLC5A8, was achieved using electrochemiluminescence. For this purpose, electrochemiluminescence of luminol loaded into the Fe 3 O 4 @UiO-66 and gold nanorod-functionalized graphite-like carbon nitride n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The produced NH 2 -MIL-53(Fe) has an excellent crystal structure, as evidenced by the XRD pattern obtained from simulated matching pattern one, which coincides with our previously reported NH 2 -MIL-53(Fe). 36,44 Notably, the peaks at 5.7, 8.9, 10. 1B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The produced NH 2 -MIL-53(Fe) has an excellent crystal structure, as evidenced by the XRD pattern obtained from simulated matching pattern one, which coincides with our previously reported NH 2 -MIL-53(Fe). 36,44 Notably, the peaks at 5.7, 8.9, 10. 1B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The powder XRD pattern of NH 2 -MIL-53­(Fe) was simulated using Crystal Diffract software and the crystallographic information file from the Cambridge Crystallographic Data Centre [CCDC 690314 for the similar parent structure, MIL-53­(Fe)]. The produced NH 2 -MIL-53­(Fe) has an excellent crystal structure, as evidenced by the XRD pattern obtained from simulated matching pattern one, which coincides with our previously reported NH 2 -MIL-53­(Fe). , Notably, the peaks at 5.7, 8.9, 10.4, 18.6, 21.17, and 25.52° in the NH 2 -MIL-53­(Fe) sample closely corresponded to the standard peaks in the card library for Fe-MOFs, suggesting successful synthesis of NH 2 -MIL-53­(Fe). The cubic lattice of AuNPs was confirmed by the XRD pattern, which showed distinct peaks at 39.6 (111), 46.15 (200), 67.15 (220), and 79.01 (311) in the 2θ values (JCPDS no.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal DNA methylation plays a significant role in the occurrence and development of THCA ( Acuña-Ruiz et al, 2022 ; Birden et al, 2022 ; Khoshfetrat et al, 2022 ). Demethylation and hypomethylation are known to increase gene expression and, in turn, regulate tumor formation, development, and metastasis ( Kazi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another sensor was proposed by Khoshfetrat et al for the simultaneous visual detection of thyroid cancer suppressor genes. Electrochemiluminescence signals were recorded on a smartphone camera with 90% sensitivity [ 29 ]. In another study, simultaneous identification of multiple bacteria was demonstrated based on a signal readout from a smartphone camera and a lateral flow assay (LFA) [ 30 ].…”
Section: Smartphone-based Sensing Methodsmentioning
confidence: 99%